The Effect Of Delay Of Clamping Umbilical Cord On Hemoglobin Level Of Newborn Baby In The Working Area Of Puskesmas Sipatana Gorontalo City Yusni Podungge Politeknik Kesehatan kemenkes Gorontalo Jurusan Kebidanan Email : yusnipodungge@poltekkesgorontalo.ac.id - YUSNI PODUNGGE (Jurnal Nasional Ilmu Kesehatan, 2019)
ABSTRACTAnemia of iron deficiency is a type of anemia often occurred on baby and its highest occurrence recorded on baby aged 6 to 24 months. There is 50% of babies suffred anemia in the age of 12 months. The anemia of iron deficiency is associated with insufficient storage of iron on the baby that disturbs development of mental and cognitive for after adult development. Time of clamping the umbilical cord plays a vital role in determining iron adequacy in a newborn baby. The research aimed to analyze the effect of the delay of clamping the umbilical cord on the hemoglobin level of the newborn baby in the working area of Puskesmas Sipatana, Gorontalo City.It is pre-experimental research with static group comparison. The population of the research was all newborn babies in the working area of Puskesmas Sipatana, while its samples were 30 babies selected through application of purposive sampling. The independent variable was the delay of clamping umbilical cord used independent t-test statistical test.Finding of the research found average Hb level of the newborn baby who was handled with the delay of clamping umbilical cord was 21,80 gr/dl and it was higher than a group of immediate clamping umbilical cord for 17,48 gr/dl. The result of data analysis obtained p-value = 0,000 and due to the p-value 0,000 was lower than 0,05; thus it affirmed to reject Ho and to accept Ha.In conclusion, there was a significant effect of the delay of clamping umbilical cord on hemoglobin level of the newborn baby in the working area of Puskesmas Sipatana. Keywords: Delay of clamping umbilical cord, Hemoglobin level of baby.